Karadeniz Bölgesi Çocuklarında Konjenital Daimi Diş Eksikliği Prevalansı - Tunç, Emine Şen; Koyutürk, Alp Erdin (My University, 2006)
Bu çalışmanın amacı; Karadeniz bölgesi çocuklarında, üçüncü büyük azı dişleri dışındaki, daimi dişlerin konjenital olarak eksikliğinin prevalansını ve dağılımını belirlemektir. Bu amaçla, 6-12 yaşlar arasındaki 981 çocuk hastanın (488 erkek, 493 kız) panoramik radyografları konjenital daimi diş eksikliği açısından değerlendirildi. Elde edilen veriler istatistiksel olarak Chi-Square ve t-testi ile değerlendirildi. Araştırmada konjenital daimi diş eksikliği prevalansı % 8,5 olarak bulundu (kızlarda %9,5 ve erkeklerde %7,7) ve cinsiyete göre istatistiksel fark gözlenmedi. En sık eksikliği gözlenen dişler sırası ile; alt ikinci küçük azı, üst yan kesici ve üst ikinci küçük azı olarak tespit edildi. Diş eksikliğinin sıklıkla simetrik olarak izlendiği, en sık simetrik diş eksikliğinin ise, alt ikinci küçük azı dişlerinde meydana geldiği belirlendi. Konjenital daimi diş eksikliği alt çenede üst çeneye göre daha fazla gözlenmesine rağmen, istatistiksel fark bulunamadı. Her iki grupta da sağ ve sol çene/erdeki eksik diş dağılımları ise benzer bulundu. Sonuç olarak çocuklardaki diş eksikliği prevalansının erken dönemde belirlenmesi alternatif tedavi yaklaşımları açısından önemlidir.

The purpose of this study was to assess the prevalence and distribution of congenitally missing permanent teeth, excluding the third molars in Blacksea region children. Panoramic radiographs of 981 children (493 girls and 488 boys) between the ages of 6 and 12 years were examined in terms of congenitally missing permanent teeth. The data were statistically evaluated by Chi-Square ve t-test. The prevalence of congenitally missing permanent teeth was 8.5% (7.7% for boys, 9.5% for girls) with no statistically significant difference between the sexes. The most commonly missing teeth were the mandibular second premolars, followed by the maxillary lateral incisors, and the maxillary second premolars. Symmetrical hypodontia was predominant, and the most commonly symmetrical hypodontia was mandibular second premolar agenesis. Congenitally missing permanent teeth was observed more than mandibula to maxilla but there were no statistically significant difference between the jaws. The distribution of missing teeth was similar between the right and the left sides of the dental arches in each group of children. As a conclusion the determination of congenitally missing permanent tooth in early period is important in terms of implementation of alternative treatment methods.
Prevalence of congenitally missing permanent teeth in Blacksea region children
Keywords: Diş Hekimliği